Drosophila Full-Length Amyloid Precursor Protein Is Required for Visual Working Memory and Prevents Age-Related Memory Impairment. - Rieche, F.; Carmine-Simmen, K.; Poeck, B.; Kretzschmar, D.; Strauss, R. (Current Biology, 2018)
The ?-amyloid precursor protein (APP) plays a central role in the etiology of Alzheimer's disease (AD). However, its normal physiological functions are still unclear. APP is cleaved by various secretases whereby sequential processing by the ?- and ?-secretases produces the ?-amyloid peptide that is accumulating in plaques that typify AD. In addition, this produces secreted N-terminal sAPP? fragments and the APP intracellular domain (AICD). Alternative cleavage by ?-secretase results in slightly longer secreted sAPP? fragments and the identical AICD. Whereas the AICD has been connected with transcriptional regulation, sAPP? fragments have been suggested to have a neurotrophic and neuroprotective role [1]. Moreover, expression of sAPP? in APP-deficient mice could rescue their deficits in learning, spatial memory, and long-term potentiation [2]. Loss of the Drosophila APP-like (APPL) protein impairs associative olfactory memory formation and middle-term memory that can be rescued with a secreted APPL fragment [3]. We now show that APPL is also essential for visual working memory. Interestingly, this short-term memory declines rapidly with age, and this is accompanied by enhanced processing of APPL in aged flies. Furthermore, reducing secretase-mediated proteolytic processing of APPL can prevent the age-related memory loss, whereas overexpression of the secretases aggravates the aging effect. Rescue experiments confirmed that this memory requires signaling of full-length APPL and that APPL negatively regulates the neuronal-adhesion molecule Fasciclin 2. Overexpression of APPL or one of its secreted N termini results in a dominant-negative interaction with the FASII receptor. Therefore, our results show that specific memory processes require distinct APPL products.